Intranasal Insulin Diminishes Postoperative Delirium and Elevated Osteocalcin and Brain Derived Neurotrophic Factor in Older Patients Undergoing Joint Replacement: A Randomized, Double-Blind, Placebo-Controlled Trial - Yang M; Zhou L; Long G; Liu X; Ouyang W; Xie C; He X (Drug Design, Development and Therapy)
Mi Yang, Lei Zhou, Ge Long, Xing Liu, Wen Ouyang, Chang Xie, Xi He Department of Anesthesia, The Third Xiangya Hospital of Central South University, Changsha, People’s Republic of ChinaCorrespondence: Xi He, Email hexitougao@163.comBackground: Brain energy metabolism disorders, including glucose utilization disorders and abnormal insulin sensitivity, are linked to the pathogenesis of postoperative delirium. Intranasal insulin has shown significant benefits in improving glucose metabolism, insulin sensitivity and cognitive function. However, its impact on postoperative delirium and insulin sensitivity biomarkers remains unknown.Aim: This randomized, double-blind, placebo-controlled trial was to evaluate whether intranasal insulin reduces the incidence and severity of postoperative delirium (POD) in older patients undergoing joint replacement, and its effect on insulin sensitivity-related biomarkers.Methods: 212 older patients (≥ 65 years) were randomly assigned to receive either 40 IU of intranasal insulin (n=106) or a placebo (n=106) for 8 days. The primary objective was to determine the incidence and severity of POD within 5 days after surgery, estimated using the Confusion Assessment Method (CAM) and the Delirium Rating Scale (DRS)-98. The secondary objective was insulin sensitivity, which was assessed using the homeostasis model Assessment of Insulin Resistance (HOMA-IR) and biomarkers, including total osteocalcin (tOC), uncarboxylated osteocalcin (ucOC), and brain-derived neurotrophic factor (BDNF).Main Results: Compared to placebo, intranasal insulin significantly reduced the incidence of delirium within 5 days after surgery (8 [8.33%] vs 23 [23.23%], P = 0.004, odds ratio [OR] = 3.33 [95% CI 1.41– 7.88]) and the severity of delirium (P< 0.001). Intranasal insulin elevated the levels of tOC, ucOC, and BDNF in the CSF on D0 (all P< 0.001) and tOC levels in the plasma on D0, D1 and D3 (all P< 0.001). It elevated ucOC levels in the plasma of the insulin group on D0 but not on D1 and D3 (all P< 0.001). Intranasal insulin administration reduced the HOMA-IR on D3 (P=0.002).Conclusion: Intranasal insulin notably reduced the incidence and severity of POD in older patients undergoing joint replacement, which may be related to the elevation in osteocalcin and BDNF levels.Trial Registry Numbers: Chinese Clinical Trial Registry (ChiCTR2300068073).Keywords: intranasal insulin, osteocalcin, postoperative delirium, brain derived neurotrophic factor, older patient